2011
DOI: 10.1371/journal.pone.0016048
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Independent Development of the Hamster Circadian Visual System

Abstract: Experience-dependent functional plasticity is a hallmark of the primary visual system, but it is not known if analogous mechanisms govern development of the circadian visual system. Here we investigated molecular, anatomical, and behavioral consequences of complete monocular light deprivation during extended intervals of postnatal development in Syrian hamsters. Hamsters were raised in constant darkness and opaque contact lenses were applied shortly after eye opening and prior to the introduction of a light-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Likewise, there is consensus that light deprivation (even over a long period of time) during development does not modify circadian rhythm synchronization to light at adult stages (Brooks et al, 2011;Palma-Gomez et al, 2018;Smith & Canal, 2009), thereby suggesting an unaltered connectivity between the RHT and SCN neurons. Moreover, a similar amount of stained RHT nerve endings that impinge on SCN neurons have been found in both light-exposed or ocular-deprived animals (Kampf-Lassin et al, 2011). These findings envisage the relevance of spontaneous neural activity in the development of the nonimage-forming visual system.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Likewise, there is consensus that light deprivation (even over a long period of time) during development does not modify circadian rhythm synchronization to light at adult stages (Brooks et al, 2011;Palma-Gomez et al, 2018;Smith & Canal, 2009), thereby suggesting an unaltered connectivity between the RHT and SCN neurons. Moreover, a similar amount of stained RHT nerve endings that impinge on SCN neurons have been found in both light-exposed or ocular-deprived animals (Kampf-Lassin et al, 2011). These findings envisage the relevance of spontaneous neural activity in the development of the nonimage-forming visual system.…”
Section: Discussionsupporting
confidence: 71%
“…In the circadian system, the effects of visual experience on the physiology of the RHT‐SCN pathway remain to be investigated. Behavioral experiments have shown that animals reared in constant darkness (DD) during early development do not affect the ability of SCN neurons to synchronize to light at adult stages (Brooks et al., 2011; Palma‐Gomez et al., 2018; Smith & Canal, 2009), even if eye‐occluded conditions are maintained for a long time (Kampf‐Lassin et al., 2011). These findings suggest that light stimulation is not critical for RHT fibers to connect and be synaptically efficient with SCN neurons, which reinforces the notion that the synaptic wiring occurring during early development in a DD environment depends only on endogenous neural activity (Katz & Crowley, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As a burrowing rodent species, Syrian hamster pups may not experience light until later than carnivore or primate species. Indeed, Syrian hamsters develop normal circadian systems without visual experience (Kampf-Lassin et al 2011). Alternatively, the RFs of cats, rats, and mice in previous studies may have refined normally during development but enlarged by the time of recording.…”
Section: Comparison With Other Speciesmentioning
confidence: 94%
“…Despite a general pattern of the PRC that is similar in gray mouse lemurs and rodents, nocturnal and diurnal rodent species exhibit phase delays almost twice as long as those of the gray mouse lemurs, as observed in the golden Hamster (Pohl, 1984) or in mice and rats (Pittendrigh and Daan, 1976b). This characteristic may be a typical primate trait, since similar observations have been made in other primate species, such as owl monkeys ( Aotus lemurinus ) (Rauth-Widmann et al, 1991), marmosets ( Callithrix jacchus ) (Wechselberger and Erkert, 1994) or squirrel monkeys ( Saimiri sciureus ) (Hoban and Sulzman, 1985).…”
Section: Daily Entrainment Of the Circadian Clock By Light And Its Chmentioning
confidence: 97%
“…To sustain circadian signals intracellularly, the negative-feedback loops between Clock/Bmal1 heterodimers and Per and Cry gene transcription are thought to be identical in diurnal and nocturnal mammals (Yu et al, 2002; Duong et al, 2011; Lande-Diner et al, 2013; Bollinger and Schibler, 2014). In addition, studies conducted in night-active and day-active mammalian species reveal that the phase-shifting effect of light is mainly efficient during the night period, regardless of the chronotype (Pohl, 1984; Takahashi et al, 1984; Hoban and Sulzman, 1985; Slotten et al, 2005; Shuboni and Yan, 2010). In the daytime, light exerts no synchronization effect during the previously described dead zone of the PRC, located between two windows of responsiveness to illumination.…”
Section: Daily Entrainment Of the Circadian Clock By Light And Its Chmentioning
confidence: 99%